2011
DOI: 10.1186/ar3353
|View full text |Cite
|
Sign up to set email alerts
|

Pain persists in DAS28 rheumatoid arthritis remission but not in ACR/EULAR remission: a longitudinal observational study

Abstract: IntroductionDisease remission has become a feasible goal for most rheumatoid arthritis (RA) patients; however, patient-reported symptoms, such as pain, may persist despite remission. We assessed the prevalence of pain in RA patients in remission according to the Disease Activity Score (DAS28-CRP4) and the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) remission criteria.MethodsData were analyzed from RA patients in the Brigham Rheumatoid Arthritis Sequential Study with data at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
180
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 210 publications
(192 citation statements)
references
References 24 publications
8
180
0
4
Order By: Relevance
“…A total of 248 patients were recruited between August 2006 and July 2011. Of these, 11 did not complete the pain questionnaires, 18 dropped out and 1 died before the first followup, and 7 had not yet reached the 12-month benchmark by March 1, 2012. We therefore report on 211 patients who completed the pain assessments at both time 994 Dobkin et al periods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 248 patients were recruited between August 2006 and July 2011. Of these, 11 did not complete the pain questionnaires, 18 dropped out and 1 died before the first followup, and 7 had not yet reached the 12-month benchmark by March 1, 2012. We therefore report on 211 patients who completed the pain assessments at both time 994 Dobkin et al periods.…”
Section: Resultsmentioning
confidence: 99%
“…For example, arthritis patients with psychological distress are more likely to experience and be disabled by pain (5,6). Lee et al (7) found that even when in remission, 12% of patients with RA report significant levels of pain that are associated with global functioning, fatigue, sleep problems, and poor self-efficacy for dealing with the disease. Little empirical work has been devoted to this topic in early IP (EIP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early arthritis, active joint inflammation causes a significant burden of pain. However, several earlier observations indicate an uncoupling of pain and joint inflammation during the disease course and show that pain may persist in inflammatory remission 4, 5. These findings indicate that pain, not directly related to inflammation, may be insufficiently controlled by antirheumatic drugs, and there is a lack of earlier studies of the pain pattern related to treatment response in early RA.…”
Section: Introductionmentioning
confidence: 92%
“…In previous consensus guidelines, remission was operationally defined as a Disease Activity Score in 28 joints using C‐reactive protein level (DAS28‐CRP) of <2.6 12. However, some patients with DAS28‐CRP <2.6 experience residual disease activity, including inflammation, pain, and joint tenderness and swelling in ankle and foot joints 5, 13, 14, 15, 16, 17, 18. Although DAS28‐CRP <2.6 no longer constitutes remission, it remains a valid treatment target.…”
Section: Introductionmentioning
confidence: 99%